Acculturation, Cultural Self, and Identity of Japanese Children in U.S. Schools: Insights from Japanese Temporary Resident and Immigrant Parents. Issue 3 (2nd July 2020) - Kayama, Misa; Yamakawa, Naomi
ABSTRACT: Relocation to a new culture has significant impacts on individuals' "self" and identity. This qualitative study examines the perspectives of Japanese temporary resident and immigrant parents on their children's acculturation to U.S. local schools and its impact on self. Japanese people, generally, are sensitive to others' responses to their struggles. Reluctance to seek formal support that can label them as "failures" may increase their vulnerability to acculturative stress. Individual interviews with 14 Japanese parents from 11 families in a southern state described the experiences of 23 children. Parents reported that language barriers and differences in school systems, particularly, have affected their children's self and identity, including a sense of inferiority and reluctance to participate in activities to protect themselves. Yet participation in non-academic activities such as sports, which do not require extensive English communication skills, helps their children develop friendships with local children and regain a positive understanding of self. Further, the time they spend with other Japanese children can relieve acculturative stress, and motivate them to participate at their local schools. The Japanese case study can broaden our perspectives on the self and acculturation of immigrant and foreign-born children, and provide insights into how we might better support them.